"Black cloud" vs. "white cloud" physicians – Myth or reality in apheresis medicine?. Issue 4 (17th August 2016) - Pham, Huy P.; Raju, Dheeraj; Jiang, Ning; Williams, Lance A.
Abstract: Background: Many practitioners believe in the phenomenon of either being labeled a "black cloud" or "white cloud" while on‐call. A "white‐cloud" physician is one who usually gets fewer cases. A "black‐cloud" is one who often has more cases. It is unclear if the designation is only superstitious or if there is some merit. Our aim is to objectively assess this phenomenon in apheresis medicine at our center. Methods: A one‐year prospective study from 12/2014 to 11/2015 was designed to evaluate the number of times apheresis physicians and nurses were involved with emergent apheresis procedures between the hours from 10 PM and 7 AM. Other parameters collected include the names of the physician, apheresis nurse, type of emergent apheresis procedure, day of the week, and season of the year. Results: During the study period, 32 emergent procedures (or "black‐cloud" events) occurred. The median time between two consecutive events was 8 days (range: 1–34 days). We found no statistically significant association between the "black‐cloud" events and attending physicians, nurses, day of the week, or season of the year by Chi‐square and Fisher's analyses. However, exploratory analysis using association rule demonstrated that "black‐cloud" events were more likely to happen on Thursday (2.19 times), with attending physician 2 (1.18 times), and during winter (1.15 times). Conclusion: The results of this pilot study may support the common perception that some physicians or nurses are either "black cloud" or "white cloud". A larger, multi‐center study population is needed to validate the results of this pilot study.